2016
DOI: 10.1093/treephys/tpw044
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of prescribed fire onPinus rigidaMill. in upland forests of the Atlantic Coastal Plain

Abstract: A comparative analysis of the impacts of prescribed fire on three upland forest stands in the Northeastern Atlantic Plain, NJ, USA, was conducted. Effects of prescribed fire on water use and gas exchange of overstory pines were estimated via sap-flux rates and photosynthetic measurements on Pinus rigida Mill. Each study site had two sap-flux plots, one experiencing prescribed fire and one control (unburned) plot for comparison before and after the fire. We found that photosynthetic capacity in terms of Rubisco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
3
1
Order By: Relevance
“…It was easier to assign an ecophysiological value to PyC amendment. We found a more modest increase (about 12%) in iWUE fostered by PyCF or PyCA treatments than other investigators (Carlo et al, 2016), who reported a 22% increase in pitch pine photosynthetic iWUE based on PyCF alone. There are bound to be anomalies which arise between PyC analytes for a considerable number of reasons.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…It was easier to assign an ecophysiological value to PyC amendment. We found a more modest increase (about 12%) in iWUE fostered by PyCF or PyCA treatments than other investigators (Carlo et al, 2016), who reported a 22% increase in pitch pine photosynthetic iWUE based on PyCF alone. There are bound to be anomalies which arise between PyC analytes for a considerable number of reasons.…”
Section: Discussioncontrasting
confidence: 81%
“…One prominent benefit is ecophysiological; it results from nutrient mobilization and moisture retention. As an increase in photosynthetic intrinsic water use efficiency or iWUE (Renninger et al, 2013;Carlo et al, 2016), iWUE is derived from stable isotope analysis (stated as per mils: parts per thousand, notated as (…”
Section: Introductionmentioning
confidence: 99%
“…However, foliar N content of sub-canopy and understory species increased following defoliation, and thus little net change in the total amount of N in foliage occurred and ecosystem WUE was not significantly different pre-and post-disturbance [37,57,63]. Increased foliar N levels and enhanced maximum assimilation rates in the remaining pine needles were observed following relatively intense prescribed burns in the PNR, but not during low-intensity burns [25,64]. Increased N levels and photosynthetic rates following wildland fires are likely related to the transient pulse of inorganic N associated with consumption of forest floor material, in addition to pyro-mineralization and release of phosphorus and basic cations [65,66].…”
Section: Discussionmentioning
confidence: 96%
“…Increased N levels and photosynthetic rates following wildland fires are likely related to the transient pulse of inorganic N associated with consumption of forest floor material, in addition to pyro-mineralization and release of phosphorus and basic cations [65,66]. Enhanced photosynthetic rates in pine needles did not persist beyond the first growing season following each fire [25,64].…”
Section: Discussionmentioning
confidence: 99%